Paulus og neurobiologien - Engberg-Pedersen, Troels (Dansk Teologisk Tidsskrift, 2011)
This review discussion of Colleen Shantz, Paul in Ecstasy etc. describes the main argument of the book, criticizes various details of its argumentation and concludes with a general assessment, which basically applauds the focus on ‘religious experience’ and the attempt to bring in both contemporary neuroscience and social anthropology to elucidate Paul and Pauline Christianity, but also queries whether these modern disciplines are at present sufficiently precise for it to be possible to draw any firm conclusions regarding the historical material.